Investigation of the magnification of digital panoramic radiographs in different regions of the jaws - Mehrdad Abdinian; Fatemeh Soheilipour; Rahman Nazeri; Sajad Ghorbanizadeh (Wolters Kluwer Medknow Publications, 2016)
Introduction: Distortion and geometric changes are major problems in panoramic radiography. As the digital panoramic machines are diverse and widely used, providing precise dimensions in each structure in the radiographs can improve their application. The aim of this study was to examine the horizontal and vertical magnification of digital panoramic radiographs in different areas of the jaws. Materials and Methods: In this descriptive analytical study, 10 dry human skulls were marked by gutta-percha in different horizontal and vertical dental areas. The radiographs were then prepared from each skull in the optimum situation recommended by the manufacturer in two digital panoramic machines. (Planmeca Promax Scara 3 and Instrumentarium-OP200). Measurements of the skulls and radiographs were independently carried out by two observers, and the data were analyzed by SPSS 18 software. Horizontal and vertical magnifications were computed in each region, and the results were analyzed by t-test and interclass correlation coefficient (α = 0.05). Results: The mean magnifications of both vertical and horizontal dimensions in different regions were different in both machines. The vertical and horizontal dimensions of Planmeca Promax Scara 3 and vertical dimensions of Instrumentarium-OP200 were clinically reliable and close to real dimensions. The horizontal dimensions of Instrumentarium-OP200 were much different from real dimensions. (P > 0.05). Conclusion: The mean magnifications of both vertical and horizontal dimensions were different in various regions of the jaws. Measurements in vertical dimensions were more reliable than horizontal ones.